Comparative Study of Lung Functions in Women Working in Different Fibre Industries - Khanam, F; Islam, N; Hai, MA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):174-9. The abstract of this article is available on the PubMed website